Real‐world experience of consolidation durvalumab after concurrent chemoradiotherapy in stage III non‐small cell lung cancer - Yiqing Huang; Joseph J. Zhao; Yu Yang Soon; Alvin Wong; Folefac Aminkeng; Yvonne Ang; Yugarajah Asokumaran; Jia Li Low; Matilda Lee; Joan R. E. Choo; Gloria Chan; Adrian Kee; et al. (Thoracic Cancer, 2022)
Abstract Background Durvalumab consolidation is associated with improved survival following concurrent chemoradiotherapy (CCRT) in patients with stage III non‐small cell lung cancer (NSCLC). Given the heterogeneity of stage III NSCLC patients, in this study we evaluated the efficacy and safety of durvalumab in the real‐world setting. Method Unresectable stage III NSCLC patients were retrospectively studied: one cohort received CCRT, another had CCRT‐durvalumab. Primary endpoints were progression‐free survival (PFS) and overall survival (OS), secondary endpoints were relapse rate and safety. In CCRT‐durvalumab cohort, association between blood markers with survival and pneumonitis risk were analyzed. Results A total of 84 patients were enrolled: 45 received CCRT, and 39 received CCRT‐durvalumab. Median PFS was 17.5 months for CCRT‐durvalumab and 8.9 months for CCRT‐alone (HR 0.47, p = 0.038). Median OS was not‐reached for CCRT‐durvalumab and 22.3 months for CCRT‐alone (HR 0.35, p = 0.024). Both EGFR‐positive and wild‐type (WT) patients had numerically improved PFS with durvalumab consolidation compared to CCRT‐alone, 17.5 versus 10.9 months and 11.8 versus 6.63 months, respectively (interaction p‐value = 0.608). Grade 2+ pneumonitis was detected in 25% of patients in the durvalumab cohort. Most pneumonitis occurred at 3.5 weeks after durvalumab initiation. Baseline neutrophil‐to‐lymphocyte ratio (NLR) ≥ 3 and ≥5 were associated with shorter PFS with durvalumab. Week 6 platelet‐lymphocyte‐ratio ≥ 180 was associated with a lower risk of pneumonitis. Conclusion In this real‐world study, durvalumab consolidation post CCRT was associated with a statistically significant improvement in PFS and OS. Effect of durvalumab on PFS was not modified by EGFR status. Active surveillance for pneumonitis is crucial. Baseline NLR may help to predict the benefit of treatment with durvalumab.